An Integration Of The Seismic Methods In Characterization Of An Unsaturated Granitic Residual Soil Site - Rosyidi, Sri Atmaja P; Nayan, Khairul Anuar Mohd (Jurnal Semesta Teknika, 2006)
A comprehensive seismic survey encompassing the seismic refraction and the downhole method have been carried out in order to characterize a site of granitic residual soil. The seismic refraction was found to be useful in the initial modeling of the subsurface and has managed to identify the water table, a bolder and the bedrock level satisfactorily. From the downhole seismic, P-wave velocity was found to be responsived to lithology and the water table, while the S-wave velocity was found to be able to characterise the residual soil in terms of their weathering grades. Correlations between the S-wave velocity (Vs) and dynamic shear modulus (Gseis) were established with the SPT (N) and the static unload reload shear modulus (Gur)of the pressuremeter tests. The relationship of Vs = 2.89N + 167.84 and Gseis (MPa) = 2.39Gur + 36.03 were obtained in this study.